2022
DOI: 10.1039/d2tc03671a
|View full text |Cite
|
Sign up to set email alerts
|

Programming multicolour micro-patterns via regional polymer-stabilized heliconical soft architecture

Abstract: Structural colours have broad applications in advanced photonics due to the versatile advantages of fade-resistant, high resolution and saturation. Nevertheless, leveraging the structural colours of adaptive systems with dynamical wide-colours...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The orienting agent SD1 was spin-coated on the surface of the glass substrate; then, a DMD-based microlithography system was used to orient SD1 in micro-areas. After injecting the chiral LCP mixture, the LCP monomers and ap - 1o in the exposed area would be arranged according to the mask pattern due to the anchoring force of the orienting layer. , The entire LC cell was exposed to UV light for maintaining the helical arrangement and reconfiguring optical microstructures on the LCP film (Figure a). Inspiringly, the optical microstructure remained in its initial arrangement without obvious damage, and the reflection band of the oriented region showed a blue shift about 40 nm after photopolymerization (Figures S18–S20), which can be attributed to the slight decrease in helical pitch induced by the volume shrinkage after polymerization and crosslinking reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The orienting agent SD1 was spin-coated on the surface of the glass substrate; then, a DMD-based microlithography system was used to orient SD1 in micro-areas. After injecting the chiral LCP mixture, the LCP monomers and ap - 1o in the exposed area would be arranged according to the mask pattern due to the anchoring force of the orienting layer. , The entire LC cell was exposed to UV light for maintaining the helical arrangement and reconfiguring optical microstructures on the LCP film (Figure a). Inspiringly, the optical microstructure remained in its initial arrangement without obvious damage, and the reflection band of the oriented region showed a blue shift about 40 nm after photopolymerization (Figures S18–S20), which can be attributed to the slight decrease in helical pitch induced by the volume shrinkage after polymerization and crosslinking reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the reflective color after photopolymerization matched the wavelengths of 532 and 633 nm of circularly polarized light with 2.05 and 1.98% R5011, respectively, showing the corresponding optical diffraction. Here, four optical microstructuresperiodic stripes, periodic concentric circles, 2D gratings, and fork-shaped gratings with RGB reflection colorswere programmed on the photoresponsive LCP film and successfully produced the corresponding optical diffraction with sharp edges, which represented a significant step toward developing advanced flexible anti-counterfeiting materials (Figure b) …”
Section: Resultsmentioning
confidence: 99%
“…Zheng et al recently reported tunable color-based anti-counterfeiting and light encryption of several cholesteric liquid crystal systems. 49–51 Light-induced dynamic helical transformation of chiral photo-switches in cholesteric liquid crystals can control the color tuning, erasing, reversibility, multistability and viewing angle dependence of pre-recorded patterns. These properties lead to digitally controllable, selectable and extractable multistable reflection states that can be used for anti-counterfeiting or encryption.…”
Section: Resultsmentioning
confidence: 99%
“…50 They also demonstrated that programmed micro-patterned heliconical structures prepared by local polymer stabilization can be used for anti-counterfeiting applications by controlling the applied electric field to exhibit high color saturation and full color range, including visible light. 51…”
Section: Resultsmentioning
confidence: 99%
“…electrochromic, thermochromic, mechanochromic or photochromic materials. 13–17 Most of the current research is focused on the exploitation of different stimuli as triggers, the intrinsic function and various designs for different applications. However, few groups have reported the integration of shape reconfiguration and color change into a single system.…”
Section: Introductionmentioning
confidence: 99%